Plastic Pollution as Waste Colonialism in Moananui - Fuller S; Ngata T; Borrelle SB; Farrelly T (University of Arizona Libraries, 2022)
Plastics pollution is a global, relational, integrated, and intersectoral issue. Here, we undertook narrative analysis of semi-structured interviews with nineteen key plastic pollution decision-makers. They offered a contextual lens to understand challenges facing Pacific Island (Te Moananui) nations in preventing plastics pollution. We build on the work of Ngata (2014-2021) and Liboiron (2014-2021) to situate the narrative analysis within a "waste colonialism" framework. We argue that plastics pollution as waste colonialism transcends environmental, policy, and industry concerns. "Indigenous political ecologies" of plastics pollution provide an understanding by which plastics pollution prevention can be examined at multiple scales. These include, at the international level: trade agreements and import dependency, donor aid and duplication, and transnational industry influence. At the local level: pressure from local plastics manufacturers, importers and suppliers, and barriers to accessing the latest science. Located within a global and regional context, our findings capture the systemic and long-standing impacts of colonialism on Indigenous responses to plastics pollution prevention and management, highlighting its effects on human and environment health and wellbeing. Sustainable solutions to plastics pollution for Te Moananui require the centering of its peoples and their deep, lived, and intergenerationally transmitted knowledges in the identification of challenges and solutions, the implementation of activities, and amplification of a shared regional voice.
Keywords: 16 Studies in Human Society